Inclusive Teaching Strategies and Student-Perceived Outcomes in Primary Inclusive Schools: Insights from Jabodetabek, Indonesia - Rahmadani, Anisa; Rahmawati, Yuliana Mukti; Nur Syamsina, Rahmi (Universitas Pendidikan Mandalika, 2025)
This study aims to investigate the correlation between inclusive teaching strategies and their impact on the outcomes of inclusive education. Using a descriptive quantitative design, this study involved inclusive elementary school students (n = 339) in the Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. Data were collected through the Perception of Inclusion questionnaire (n = 12) and Inclusive Teaching Strategies Scale (n = 29). Hierarchical regression tests were used to examine the relationship between variables and dimensions of teacher teaching strategies that most influenced inclusive outcomes. The results showed that Values & Attitudes accounted for 37% of the variance in inclusion outcomes (R² = 0.37; β = 0.60, p < 0.01). Adding Management & Environment increased the explained variance to R² = 0.41 (β = 0.26, p < 0.01), and adding Teaching & Instruction further raised it to R² = 0.43 (β = 0.18, p < 0.01). In the final model, all subscales remained significant (Values & Attitudes β = 0.35; Management & Environment β = 0.20; Teaching & Instruction β = 0.18; all p < 0.01), identifying teacher Values & Attitudes as the strongest predictor. Findings underscore the need to prioritize teacher mindset development, proactive classroom management routines, and differentiated instruction to strengthen inclusive outcomes. Stakeholders should implement programs that raise awareness and promote diversity among students to foster more positive attitudes and values toward inclusion.